AVALIAÇÃO DE DESEMPENHO DOS SETORES PRODUTIVOS DE UM HOSPITAL ESCOLA VETERINÁRIO: USO DE UM MODELO HIERARQUICO MULTICRITERIAL. - Matias, Antero Paulo dos Santos (2008)
The Veterinary Medicine course is composed essentially of theoretical and practical course works that is developed by the diverse disciplines that exists in the curricula matrix of the course. For the practical courses, principally those related to the professional disciplines to be lectured, the course must have a Teaching Hospital. This Teaching Hospital has as a mission: Teaching (Practical Lectures), Research (development of new technologies and knowledge) and Extension or Assistance (Attendance it the will and anxiety and necessity of the community with it operates Even though it reflect the context of the course, the hospital must present some elements of control, no only to meet the financial standpoint but also in accordance with its operating premise so as to meet the client satisfaction and those who work there not to mention the community at large. The process of managerial control is the process that leaders have to ensure that the other members of the organization do follow the strategies determined. Health and educational organizations develop their activities through their cost or center of responsibilities, which exist in order to meet their purpose. As the organization is a set center of responsibilities, each center of responsibility would have to comply with their own strategies to enhance the achievement of organizational goals. The General Manager of the hospital decides on what strategy to follow in congruence with the premises or goals of the organization. This decision should be based on parameters and results to be achieved through decision tools. Many organizations use the performance evaluation results of their centers of responsibilities to take decisions. The present study is an action research, which proposes the presentation of a theoretical model, that is represented by a tool that will provide performance evaluation decision indicators with the premises of education, research and assistance as well as embracing financial indicators that management would oversee and decide which path to follow, thus serving as an enhancement to administrative decisions. We compared the classification and ranking of each of the productive sectors in accordance with the financial performance, in this case, the contribution margin and after the calculations presented we observed a change in the ranking of the sectors. This model was based on multicriteria ranking tool. The most important factor was to understand that all productive sectors had their ranking altered after the calculations presented with the tool. Thus, this tool would become a form of broader decision procedure that contemplates other criteria, or in this case, assumptions that are imperative to the decision, and also very useful to identify between the premises which present variable deviate performance. Based on our findings, we conclude that managers could implement corrective measures aiming at ameliorating operating weaknesses, seeking targets that can be achieved in determining financial contribution, and in this the case, to achieve them.(AU)